The Minimum of Teaching Facilities in Dta Al-Hikmah, Kutaagung Village Has Impact on Children's Learning Interest - Wahyuni, Sri; Supriatiningsih, Risti; M, Maulana Rizala Nur; Syaputra, Irsyaad Akbar; Dianah, Rana; Rahman, Indra; Mansyur, Gilar Muhammad; Aprilia, Dara; Ramadan, Dani Muhamad; Thayeb, Ajeng Amanda; Jaelani, Zuli; Muhajirin, Muhammad (AbdimasMu UMTAS, 2023)
The provision of learning facilities and interest in learning is an alternative strategy for learning in schools, in which students and assisting in problems related to the subject matter in each subject will encourage students to develop all their potential optimally regarding the material and answers to existing questions and questions, so that learning outcomes at school are increasing. This study aims to determine the impact of the lack of facilities in DTA Al-Hikmah Dusun Kutaagung on students' interest in learning. The method used in this study is a qualitative descriptive method. The main resource persons in this study were two people, namely the Head of Kutaagung Village and the DTA Teacher Al-Hikmah Dusun Kutaagung. Data collection techniques used are observation and interviews. From the results of research conducted that the lack of learning facilities in DTA Al-Hikmah Dusun Kutaagung affects student interest in learning which is indicated by the attendance list data of students who do not have a commitment to attend learning every day. This proves that teaching and learning facilities have an impact on students' interest in learning to increase the potential that exists in each student's personality.